PENTINGNYA KERJASAMA ANTARA PEMERINTAH INDONESIA DENGAN INTERNATIONAL ORGANIZATION OF MIGRATION (IOM) - ARSYAD IMAM BAIHAQI; SALSABILA PUTRI SALAM; HARDYANO FATIH WARGANEGARA (KULTURA DIGITAL MEDIA ( Research and Academic Publication Consulting ), 2021)
Indonesia is the biggest archipelago country in the world. Indonesia also has a strategic location. This can be seen from the geographical position of Indonesia, which is located in the Southeast Asia region, bordering 2 continents, namely the continents of Asia and Australia/Oceania, and 2 oceans, namely the Indian and Pacific oceans. With the central and strategic position that Indonesia have, this position makes Indonesia a route in every activity, both for tourism or business. The strategic location of Indonesia can certainly be utilized by irresponsible individual. Such as the existence of human trafficking and people smuggling activity, whether it is from within the country or from outside the country. This individuals or syndicate has clearly collaborated from internal and external parties, as it must involve a lot of parties. Therefore, to overcome such problems, it is important to maintain cooperation between the government of Indonesia and the international organization of migration (IOM)